Cloud-assisted rendering support for mobile online gaming (Part C) - Seet, Ronald Seng Jian (2015)
The gaming industry has grown greatly in the recent times, especially so for mobile games. As such, we look at cloud gaming to overcome one of the major hurdles in games, hardware constraints. However, cloud gaming has its weaknesses such as being network dependent and losing out to regular games in terms of response time. In this project, the focus will be on optimizing the bandwidth usage on an existing cloud gaming system. The report also covers some of the fixes done to the system. To optimize the bandwidth usage, the techniques involve modification of the video encoding output bitrate and resolution. From this project, it can be seen that using video streaming over VNC image transmission reduces minimal bandwidth usage to a third. Furthermore, the minimal bandwidth usage can be further reduced to another third when using the minimal bitrate for the video but at the cost of quality. In general much of the techniques are useful for managing the bandwidth usage. However, there are much better alternatives to improve bandwidth efficiency.